Analisis Sektor Ekonomi Potensial Kabupaten Batang Hari - Wiyan Mailindra (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
This research uses LQ Analysis Tool, and Pearson Correlation. As for the operating variable in this study is the GDP at constant prices, Economic Growth, Growth Sector, And Poverty in Batanghari, with the title